2018
DOI: 10.1158/0008-5472.can-17-1236
|View full text |Cite
|
Sign up to set email alerts
|

LSD1 Stimulates Cancer-Associated Fibroblasts to Drive Notch3-Dependent Self-Renewal of Liver Cancer Stem–like Cells

Abstract: Cancer stem-like cells (CSC) in hepatocellular carcinoma (HCC) are thought to mediate therapeutic resistance and poor survival outcomes, but their intrinsic and extrinsic control is not well understood. In this study, we found that the chromatin modification factor LSD1 is highly expressed in HCC CSC where it decreases during differentiation. LSD1 was responsible for maintaining CSC self-renewal and tumorigenicity in HCC, and its overexpression was sufficient to drive self-renewal of non-CSC. Levels of acetyla… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(87 citation statements)
references
References 50 publications
(67 reference statements)
1
77
0
2
Order By: Relevance
“…More recently, Liu et al confirmed several of the above results, including the contribution of high LSD1 levels to stemness and tumor growth, in a differently isolated HCC-CSC population (based on Nanog levels) [102]. Moreover, they investigated the regulation of LSD1 in HCC-CSCs and provided evidence that Notch signaling induced SIRT1 expression leading to LSD1 deacetylation, activation and stabilization.…”
Section: Lsd1 In Hepatocellular Carcinoma Stem Cellsmentioning
confidence: 75%
See 1 more Smart Citation
“…More recently, Liu et al confirmed several of the above results, including the contribution of high LSD1 levels to stemness and tumor growth, in a differently isolated HCC-CSC population (based on Nanog levels) [102]. Moreover, they investigated the regulation of LSD1 in HCC-CSCs and provided evidence that Notch signaling induced SIRT1 expression leading to LSD1 deacetylation, activation and stabilization.…”
Section: Lsd1 In Hepatocellular Carcinoma Stem Cellsmentioning
confidence: 75%
“…Moreover, they investigated the regulation of LSD1 in HCC-CSCs and provided evidence that Notch signaling induced SIRT1 expression leading to LSD1 deacetylation, activation and stabilization. Finally, they provided in vivo evidence that the tumor microenvironment-through activated cancer-associated fibroblasts-stimulated Notch3 signaling, which, in turn, enhanced LSD1 expression to facilitate tumor growth [102].…”
Section: Lsd1 In Hepatocellular Carcinoma Stem Cellsmentioning
confidence: 99%
“…It has been demonstrated that NOTCH2 is involved in self‐renewal of CSCs in HCC . NOTCH3 also reportedly regulates the stemness of CSCs of HCC . Although no functional relationship between CD44s and NOTCH3 in HCC has been reported, Ma Y, et al observed that NOTCH3 was upregulated in nonsmall cell lung cancer tissues from chemoresistant patients and was positively associated with CD44 .…”
Section: Discussionmentioning
confidence: 99%
“…In breast cancer, CAFs can also promote the cancer stem cell phenotype by secreting CCL2 (Tsuyada et al, 2012). Induction of Notch3 by CAFs is also associated with an increase in cancer stem cells in hepatocellular carcinoma (HCC) (Liu et al, 2017a). The Notchmediated interaction between cancer cells and the mesenchymal compartment is also involved in resistance to chemotherapy.…”
Section: Notch-mediated Interaction With and Activation Of Fibroblastsmentioning
confidence: 99%